2017
DOI: 10.1186/s13046-017-0530-4
|View full text |Cite
|
Sign up to set email alerts
|

Benserazide, a dopadecarboxylase inhibitor, suppresses tumor growth by targeting hexokinase 2

Abstract: BackgroundHexokinase (HK) is the rate-limiting enzyme in the first reaction of glycolysis. And Hexokinase 2 (HK2) is most closely related to malignant tumor which expresses at higher level compared with normal cells. HK2 plays a pivotal role in tumor initiation and maintenance, which provides a new target for cancer therapy.MethodsStructure-based virtual ligand screening was used in hit identification from ZINC Drug Database. Microscale thermophoresis assay was performed to evaluate the binding affinity. Enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 37 publications
0
58
0
1
Order By: Relevance
“…With extensive studies, including the present investigation, showing that HK2 is a master promoting factor in different stages of carcinogenesis ( Supplementary Table 4), much efforts were put in exploring HK-mediated tumor inhibitors, despite that no potent drugs targeting HK2 are yet available in clinic (80)(81)(82)(83)(84). Taking the most promising HK2-targeting drug, 3-bromopyruvate (3-BP), as an example, although single treatment of 3-BP, at the appropriate dose and formulation, could effectively destroy glycolytic tumors and seems to be non-toxic to all sorts of vertebrates, certain failure cases were still reported in clinical test (83).…”
Section: Discussionmentioning
confidence: 97%
“…With extensive studies, including the present investigation, showing that HK2 is a master promoting factor in different stages of carcinogenesis ( Supplementary Table 4), much efforts were put in exploring HK-mediated tumor inhibitors, despite that no potent drugs targeting HK2 are yet available in clinic (80)(81)(82)(83)(84). Taking the most promising HK2-targeting drug, 3-bromopyruvate (3-BP), as an example, although single treatment of 3-BP, at the appropriate dose and formulation, could effectively destroy glycolytic tumors and seems to be non-toxic to all sorts of vertebrates, certain failure cases were still reported in clinical test (83).…”
Section: Discussionmentioning
confidence: 97%
“…The high IC 50 indicated that benserazide is relatively less toxic compared to the anticancer drugs. Several other studies have also reported the toxicity of benserazide in the similar range, for example the IC 50 of benserazide in the cell lines such as SW480, Lovo, HCT116, and MCF7 was 143, 151, 181 and 186 μM respectively . The cytotoxicity of benserazide on HeLa cells shows its potential for repurposing it as an anticancer agent.…”
Section: Resultsmentioning
confidence: 59%
“…The bioactive compounds that target the Warburg effect to fight cancer can be summarized as being members of two groups: metabolite analogs, for example, 3‐bromopyruvate, and secondary metabolites from natural sources. A series of bioactive natural products have been identified that inhibit HK2, including heterocycles, 2,6‐disubstituted glucosamines, and benserazide . The alkaloids of the PTM class and related compounds are a small group of approximately 30 metabolites with a unique polycyclic skeleton, and macrolactams, which are widely produced by the genera Lysobacter , Saccharophagus, and Streptomyces .…”
Section: Resultsmentioning
confidence: 99%
“…A series of bioactive natural products have been identified that inhibit HK2, including heterocycles, 2,6-disubstituted glucosamines, and benserazide. 39,40 The alkaloids of the PTM class The ECAR was normalized to the total protein content between groups prior to making comparisons and is reported as mpH/min. F, Quantification of glycolytic capacity.…”
Section: Identification Of the Ika Binding Targetmentioning
confidence: 99%